Primary school pupils' images of mathematics. Issue 1 (July 2021) - Ismail, Nazihah; Abdullah, Nur Hidayah Masni; Osman, Roselah; Ramli, Nazirah; Hilmi, Zulkifli Ab Ghani
Abstract: Images of mathematics are one of the critical elements of students' knowledge in mathematics learning. The knowledge is formed through students' various activities and experiences throughout their lives, including mathematics education events. This study examines the images of mathematics held by three primary school pupils of one small town located on the outskirt of Pahang. Data were collected through unstructured interview sessions and written question forms. One Year 4 male pupil, one Year 5 male pupil, and a Year 6 female pupil were selected using the convenience sampling method. Several matters related to the images of mathematics learning and metaphors related to mathematics are discussed in this paper.